Comparison of efficacy of probiotics versus tetracycline fibers as adjuvants to scaling and root planing - Lavanya Boyeena; Rekha Rani Koduganti; Veerendranath Reddy Panthula; Surya Prasanna Jammula (Wolters Kluwer Medknow Publications, 2019)
Context: Both gingivitis and periodontitis are due to the detrimental effects of the microbe-laden biofilm. The mainstay of periodontal treatment is, therefore, the disruption of this biofilm by scaling and root planing (SRP). Other treatment protocols such as systemic antimicrobials have been administered as adjuvants after scaling and root planning. However, due to antimicrobial resistance, as well as a shift of the flora from a symbiotic to a dysbiotic one, this mode of treatment has its shortcomings. Thus, local drug delivery has gained prominence as a therapeutic tool. Aims: The aim of this study is to compare the efficacy of subgingivally delivered probiotics as a monotherapy, in combination with tetracycline fibers, and tetracycline fibers alone after SRP. Settings and Design: This study was a parallel arm, randomized clinical and microbiological study. Thirty patients with chronic periodontitis aged between 20 and 50 years were selected from the outpatient ward of a tertiary referral care hospital in Hyderabad and equally divided into three groups. Materials and Methods: This study was conducted from January 2017 to February 2017 and ethical clearance was obtained from the institutional ethical committee. Statistical Analysis Used: Mean values and standard deviations were calculated for Plaque Index, Sulcular Bleeding Index (SBI), probing depth (PD), and microbial colony-forming units, for all the three groups at different time intervals. Paired "t-test" was used for intragroup comparison and Student's "t-test" for intergroup comparison. Results were regarded as statistically significant when P < 0.05. Results: Intragroup comparison yielded significant improvement in all the variables (P < 0.0001). However, intergroup comparison showed statistically significant differences pertaining to the PD (P < 0.001) and SBI only (P < 0.001), between Group A and Group B and Group B and Group C respectively. Conclusions: Group A and Group C showed better results than Group B.